The evolving virtual library, visions and cases studies, de Laverna M. Saunders - Cunha, Murilo Bastos da (Revista de Biblioteconomia de Brasília, 1996)
SAUNDERS, Laverna M. (ed.). The evolving virtual library, visions and cases studies. Medford, NJ : Information Today, 1996.153 p.